Avoidance of Contaminated Food Correlates With Low Protozoan Infection in Bonobos - Sarabian, Cécile; Belais, Raphaël; MacIntosh, Andrew J. J. (Frontiers in Ecology and Evolution, 2021)
Intense selection pressure from parasites on free-living animals has resulted in behavioral adaptations that help potential hosts avoid sources of infection. In primates, such ‘behavioral immunity’ is expressed in different contexts and may vary according to the ecology of the host, the nature of the infectious agent, and the individual itself. In this study, we investigated whether avoidance of contaminated food was associated with reduced parasite infection in sanctuary-housed bonobos. To do this, we used bonobos’ responses to soil- and fecally-contaminated food in behavioral experiments, and then compared the results with an estimate of protozoan infection across individuals. We found that avoidance of contaminated food correlated negatively with Balantioides coli infection, a potentially pathogenic protozoan transmitted through the fecal-oral route. The association between avoidance responses and parasitism were most evident in experiments in which subjects were offered a choice of food items falling along a gradient of fecal contamination. In the case of experiments with more limited options and a high degree of contamination, most subjects were averse to the presented food item and this may have mitigated any relationship between feeding decisions and infection. In experiments with low perceived levels of contamination, most subjects consumed previously contaminated food items, which may also have obscured such a relationship. The behavioral immunity observed may be a consequence of the direct effects of parasites (infection), reflecting the first scale of a landscape of disgust: individual responses. Indirect effects of parasites, such as modulation of feeding decisions and reduced social interactions – and their potential trade-offs with physiological immunity – are also discussed in light of individual fitness and primate evolution. This study builds on previous work by showing that avoidance behaviors may be effective in limiting exposure to a wide diversity of oro-fecally transmitted parasites.